Q: What equation is equivalent to 3x plus 2y -2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

This is only half of an equation. If -x^2 + 3x +2y = 0, then x^2 -3x = 2y and y = (x^2-3x)/2 Solving for x is the inverse, but difficult without a second equation.

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5

3x plus 2y can be expressed mathematically as (3x + 2y).

3x plus 2y - 3 is an expression. There can be no answer to one expression and one linear equation in two variables.

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

Related questions

3x + 2y = 8 This is an equation. It could be the equation of a line.

This is only half of an equation. If -x^2 + 3x +2y = 0, then x^2 -3x = 2y and y = (x^2-3x)/2 Solving for x is the inverse, but difficult without a second equation.

3x + 2y + 5 - 3 = 3x + 2y + 2 No further simplification is possible. This is an expression, not an equation so there cannot be a solution.

If: 3x+2y = 5x+2y = 14 Then: 3x+2y = 14 and 5x+2y =14 Subtract the 1st equation from the 2nd equation: 2x = 0 Therefore by substitution the solutions are: x = 0 and y = 7

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

3x + 5 + x + 10 + 2y 4x + 2y + 15 |:2 2x + y + 7.5 2x + y + 7.5 is equivalent to the original.

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5

If you mean: 3x+2y+6 = 0 then it is y = -1.5x-3 as a straight line equation

3x plus 2y can be expressed mathematically as (3x + 2y).

3x plus 2y - 3 is an expression. There can be no answer to one expression and one linear equation in two variables.

3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3